DEVELOPMENT OF FARM-SCALE SALINE TILAPIA HATCHERY TO ADAPT TO THE IMPACT OF GLOBAL WARMING: A TECHNO-ECONOMIC ANALYSIS (Proceedings International Conference on Fisheries and Aquaculture, 2023)
Tilapia (Orechromis sp) is a freshwater fish species that is widely cultivated because of its high survival ability, easy breeding, and high market demand. However, obtaining land for cultivation in freshwater areas is increasingly difficult because it competes with industrial and residential needs. On the other hand, more brackish water area is available due to the weakening of shrimp prices and rising sea levels caused by global warming. A team of The Agency for the Assessment and Application of Technology from 2008 to 2014, through a selective breeding process, produced saline-tolerant Indonesian Tilapia (officially named "Nila Salina"), which can adapt to high salinity. This variety is superior to other tilapia varieties, but it has yet to be widely cultivated because no hatcheries produce these tilapia seeds. This study aims to explain a feasibility study on the construction of a Nila Salina hatchery in Indramayu Regency, West Java, with a pond area of 3 hectares owned by a local farmer. The study began with a field survey, technical design, primary and secondary data collection, and analysis. Based on the analysis results, it is shown that a Nila Salina hatchery, starting with six packages of broodstock (1800 females and 600 males), can produce 6,040,000 seeds per year. Financial analysis shows that the economic parameters are pretty good, namely the NPV of IDR 2,414,811,000 and IRR of 26.93, indicating that the plan to develop a Nila Salina hatchery in Indramayu is feasible to implement.
Keywords: hatchery, Nila Salina, feasibility, global warming